Evaluation of corrosion performance of Superni 600 hung in secondary chamber of medical waste incinerator operating at 1050 °C. (2nd January 2017) - Mudgal, Deepa; Ahuja, Lalit; Singh, Surendra; Prakash, Satya
Abstract: Incineration technique is widely used to dispose of contaminated waste, municipal waste or medical waste. Burning medical waste causes formation of highly corrosive environment inside the chambers. Present study deals with the performance of Ni based Superalloy Superni 600 hanged inside the secondary chamber of medical waste incinerator for 1000 h under cyclic condition. Superni 600 showed good corrosion resistance under this environment. Formation of dense and compact layer of Cr2 O3 was observed at substrate oxide interface which acts as a diffusion barrier for corrosive species.